Microstructural and abrasive wear properties of tungsten inert gas deposited FeCrC and WC coatings on AISI 4340 steel - Buytoz, Soner; Yildirim, M. Mustafa (Carl Hanser Verlag, 2007)
The abrasive wear behaviours of high-chromium ferrochromium carbon, tungsten carbide and high-chromium ferrochromium/tungsten carbide metal matrix composite coatings were investigated. Wear tests of the coatings were carried out on a pin-on-disc apparatus at loads of 10, 20 and 30 N. The effects of load on the weight loss of composite coatings were determined. The variations of weight loss values exhibited a slight increase in the weight loss except in the case of 20 N loading and total sliding distance of 60 m. The weight loss values of the samples were found to increase with the load. The changes on the microhardness and abrasive wear rate are well agreed with the variation of the weight loss. The wear behaviour of coating materials is dependent upon the matrix microstructure and the features of dispersed carbides, such as their shape, proportion, size and distribution.
Gefüge- Und Verschleißeigenschaften von Unter Wolfram-Schutzgas Abgeschiedenem FeCrC- und WC-Schichten auf AISI 4340-Stahl
Keywords: Microhardness Characteristics; Tribological Behavior; Erosion Resistance; Stainless-Steel; Laser; Plasma; Matrix